Economic Analysis Of The Determinants Of Foreign Direct Investment (FDI) In Nigeria - Adebayo, Emmanuel Oluwagbenga; Gambiyo, Suleiman Purokayo (Archives of Business Research, 2020)
The study examined the factors that determine Foreign Direct Investment (FDI) in Nigeria. It assessed the extent to which exchange rate, interest rate, degree of trade openness affects foreign direct investment inflow to Nigeria. The study used data from Central Bank of Nigeria (CBN) Bulletin and World Bank (1981 - 2017). The results were interpreted based on the Ordinary Least Square (OLS) method, apart from series of test statistics and some diagnostics on data was performed. The estimated linear regression model reveals that the degree of openness positively and significantly affect FDI. Exchange rate has a positive but non-significant relationship with FDI and interest rate has a negative relationship with FDI, but it is not statistically significant. The study therefore recommends that economic policies that allow free trade should be formulated since macroeconomic policies are important in stabilization, enhance standard growth and improvements in the standard of living as a result of improved and higher productivity.